Interprofessional education as a method to address health needs in a Hispanic community setting: A pilot study. Issue 5 (28th August 2015) - Ryan, Mark; Vanderbilt, Allison A.; Mayer, Sallie D.; Gregory, Allison
Abstract: The Hispanic population in and around Richmond, Virginia, USA, has grown rapidly since 2000. The Richmond City Latino Needs Assessment emphasized this growth and also reported concerns regarding healthcare access. Schools of medicine, pharmacy, and nursing at Virginia Commonwealth University have partnered together with community organizations to develop and implement an interprofessional student service learning pilot program to meet community needs and provide an opportunity for enhanced learning. Community events allowed students to work on interprofessional teams to provide healthcare screenings and education to the Hispanic community. The program was evaluated by the use of a community service survey. Results indicated improved perceptions of student comfort with working with diverse patients, working on teams, and patient-centered care, as well as statistically significant improvements in student understanding of health care access and barriers, community needs, and social determinants of health. Results suggest that this community-based service-learning interprofessional experience was critical in student learning.